Penyuluhan Urgensi Legalitas Usaha Dan Pemasaran Berbasis Teknologi Bagi Pelaku Umkm Di Kelurahan Sembulang Kecamatan Galang Kota Batam - Nolla Puspita Dewi; Nicha Suwalla; Sri Yanti; Nurhatisyah Nurhatisyah; Ana Faizah; Faris Ramadhan; Benni Sumarman (Universitas Kristen Indonesia Toraja, 2023)
Galang District Is One of the Administrative Areas of Batam City Formed Based on Law Number 53 of 1999 Established on October 4, 1999, Galang District Was Effectively Run After the Inauguration of the Galang Sub-District Head by Decree of the Mayor of Batam Number: Kpts 02/III. 2000 March 2, 2000. The area of ​​Galang District is 2,018.5 km2, consisting of 350.8 km2 of land and 1,667.7 km2 of sea, with a total population of 9,025 males and 8,021 females with a total population of 17,046. The Galang District area consists of 32 RWs and 83 RTs. When viewed based on ethnicity, the Galang sub-district area has at least several ethnic groups (ethnicities) inhabiting this area, namely Malays, Javanese, Flores, Buton, Banjar, Batak and other (ethnic) tribes. Sembulang Village is in the Galang District, Batam City, Riau Archipelago Province. The results of surveys or observations, at this location there is still a lack of socialization or counseling regarding the legality of technology-based businesses and marketing in the Kelurahan and RT/RW. The businesses in Galang District range from banana chips, onion chips, cakes to birthday cakes. The implementation of community service is carried out by counseling first and then providing assistance on the practice of the counseling. Availability of experts from Batam University Lecturers, and assistant staff from students, participants (community), local officials so that this Community Service activity is carried out.